Emotional Dysregulation in Children and Adolescents With Psychiatric Disorders. A Narrative Review - Paulus, Frank W.; Ohmann, Susanne; Möhler, Eva; Plener, Paul; Popow, Christian (Frontiers in Psychiatry, 2021)
Background Emotional dysregulation (ED) is a transdiagnostic construct defined as the inability to regulate the intensity and quality of emotions (such as, fear, anger, sadness), in order to generate an appropriate emotional response, to handle excitability, mood instability, and emotional over-reactivity, and to come down to an emotional baseline. Because ED has not been defined as a clinical entity, and because ED plays a major role in child and adolescent psycho-pathology, we decided to summarize current knowledge on this topic based on a narrative review of the current literature. Methods This narrative review is based on a literature search of peer-reviewed journals. We searched the databases ERIC, PsycARTICLES, PsycINFO and PSYNDEX on June 2, 2020 for peer reviewed articles published between 2000 and 2020 in English language for the preschool, school, and adolescent age (2-17 years) using the following search terms: “emotional dysregulation” OR “affect dysregulation”, retrieving 943 articles. Results The results of the literature search are presented in the following sections: the relationship between ED and psychiatric disorders (ADHD, affective mood disorders, anxiety disorders, trauma, Posttraumatic Stress Disorder, Non-Suicidal Self-Injury, abuse and maltreatment, eating disorders, Oppositional Defiant Disorder, Conduct Disorder, Disruptive Mood Dysregulation Disorder, personality disorders, substance use disorder, Developmental Disorders, autism spectrum disorder, psychosis and schizophrenia, and Gaming Disorder), prevention, and treatment of ED. Conclusion Basic conditions of ED are genetic disposition, the experience of trauma, especially sexual or physical abuse, emotional neglect in childhood or adolescence, and personal stress. ED is a complex construct and a comprehensive concept, aggravating a number of various mental disorders. Differential treatment is mandatory for individual and social functioning.